In Vitro Fertilization and Early Pregnancy Outcomes After Coronavirus Disease 2019 (COVID-19) Vaccination. Issue 4 (25th April 2022) - Aharon, Devora; Lederman, Matthew; Ghofranian, Atoosa; Hernandez-Nieto, Carlos; Canon, Chelsea; Hanley, William; Gounko, Dmitry; Lee, Joseph A.; Stein, Daniel; Buyuk, Erkan; Copperman, Alan B.
Abstract : Coronavirus disease 2019 (COVID-19) mRNA vaccination is not associated with adverse outcomes for controlled ovarian stimulation or frozen embryo transfer among patients undergoing in vitro fertilization. Abstract : OBJECTIVE: To assess whether coronavirus disease 2019 (COVID-19) mRNA vaccination is associated with controlled ovarian hyperstimulation or early pregnancy outcomes. METHODS: This retrospective cohort study included patients who underwent controlled ovarian hyperstimulation or single euploid frozen-thawed embryo transfer at a single academic center. Patients fully vaccinated with a COVID-19 mRNA vaccine were compared with unvaccinated patients who cycled during the same time period. The primary outcome was the fertilization rate for controlled ovarian hyperstimulation and the clinical pregnancy rate for frozen-thawed embryo transfer. Secondary outcomes for controlled ovarian hyperstimulation included eggs retrieved, mature oocytes retrieved, mature oocytes ratio, blastulation rate, and euploid rate. Secondary outcomes for frozen-thawed embryo transfer included pregnancy rate, ongoing pregnancy rate, biochemical pregnancy loss rate, and clinical pregnancy loss rate. RESULTS: Among 222 vaccinated patients and 983 unvaccinated patients who underwent controlled ovarian hyperstimulation cycles between February and September 2021, there was no association on adjusted analysis between COVID-19 vaccination and fertilization rate (β=0.02±0.02, P =.20) or any of the secondary outcomes assessed: eggs retrieved (β=0.01±0.57, P =.99), mature oocytes retrieved (β=0.26±0.47, P =.58), mature oocytes ratio (β=0.02±0.01, P =.12), blastulation rate (β=0.02±0.02, P =.27), or euploid rate (β=0.05±0.03, P =.08). Among 214 vaccinated patients and 733 unvaccinated patients undergoing single euploid frozen-thawed embryo transfer, adjusted analysis demonstrated no significant association between vaccination and clinical pregnancy (adjusted odds ratio [aOR] 0.79, 95% CI 0.54–1.16) or any of the secondary outcomes: pregnancy (aOR 0.88, 95% CI 0.58–1.33), ongoing pregnancy (aOR 0.90, 95% CI 0.61–1.31), biochemical pregnancy loss (aOR 1.21, 95% CI 0.69–2.14), or clinical pregnancy loss (aOR 1.02, 95% CI 0.51–2.06). CONCLUSION: Administration of COVID-19 mRNA vaccines was not associated with an adverse effect on stimulation or early pregnancy outcomes after IVF. Our findings contribute to the growing body of evidence regarding the safety of COVID-19 vaccination in women who are trying to conceive.